Strategi Peningkatan Predikat Daerah Tertinggal di Kabupaten Pandeglang Provinsi Banten - Ardiyansah Ardiyansah (Universitas Serang Raya, 2020)
The Village Fund allocation which is given directly to the village government is expected to be able to increase the income of the village community, not only improve the quality of human life, but also increase the income of the village community. The problem of disadvantaged areas is not only the focus of attention of the Central Government but also the Provincial Government. The designation of Pandeglang Regency as a disadvantaged area can be seen from several aspects including regional financial revenue, Human Development Index and the level of the people's economy which is indicated through the unemployment rate of Pandeglang people and the comparison of the number of poor people in regencies and cities throughout Banten Province. This study aims to know how the Pandeglang Regency strategy in improving the predicate of disadvantaged areas. Several improvements have been made in various sectors to improve the predicate of disadvantaged areas in Pandeglang Regency, among others, by implementing a strategy of efficient use of the budget through trimming several programs whose impact on increasing the increase in SAKIP assessments annually. The strategy paid off with an increase in SAKIP assessments that had an impact on increasing the predicate of disadvantaged areas. In addition Pandeglang Regency has also carried out an economic development scheme in increasing the predicate of disadvantaged areas through a scheme initiated by the Ministry of PDT, namely by Transportation from Farmers, Ports and Consumers, Smart Farming Scheme, and Data Collection Scheme Number of fruit trees in disadvantaged areas.